Assessment of development form and its impact on the modal split and trip generation for low-income commercial developments - Botha, Marlyn Lloyd (Department of Civil Engineering, 2019)
This topic of research was motivated through my extensive interaction in the development field and a key element which was recognized with numerous development assessments within the City of Cape Town, was the fact that our current legislation or standards applied in South Africa do not accurately inform commercial developments within low-income areas. It was observed that the South African standards and policies rely heavily on international standards which focus on private vehicle movement and networks planning which is geared for mobility, whereas South Africa and in particular metropolitan Cape Town has unique characteristic due to the City Planning Structure which was shaped by a flawed political system. The objective of this dissertation is therefore firstly to assess the impact which the built environment (TOD and TND) has on the modal split and trip generation for low income commercial developments, secondary to draw a comparison between the actual operation of low income developments and the accepted trip generation rates used in South Africa, thirdly, to assess the unique characteristics of low income developments within a local context. With this problem statement in mind the aim of this dissertation is therefore to, firstly, to establish a better understanding of the modal split and trip generation for low income commercial developments, secondly, to establish a trip generation rate which is more compatible with developments within low-income communities; and lastly to establish the benefits which can be attained through appropriate development form implementation within the low-income. The literature review section of this dissertation will review academic literature as well as recent policy documents which investigate the relationship between the development form and the impact on traffic patterns, trip generation and modal splits of development. The literature review also establishes common trends and understandings when investigating/reviewing complex data of this nature. It is also the aim of the literature review to set a foundation for the site investigation and analysis process which will be undertaken as part of this dissertation. A critical aspect of this research was the site selection process as this has a direct bearing on the outcomes of the analysis and the accuracy of the results. It is therefore critical to note that the three sites selected for this research were selected based on stringent criteria. With the site selection approach it was a key aspect to keep as many of externalities or external factors constant (Ceteris Paribus) and in this way the results would emphasize the impact of the development form on the trip generation, traffic patterns and the modal split of these developments (if any). The data collection process was done using two distinct survey methods based on the level of technology available at the sites investigated. The first method used was data collection using recorded camera surveillance footage obtained from the centre management. The second method was a manual survey method done by individuals employed at the sites and this was used where electronic data was not available. The survey/data collection process was also broken up into 4 phases, of which the first of these processes was a pilot survey which was undertaken at one of the sites earmarked for the investigation. The aim of this pilot survey was to identify the any shortcoming in the data collection process and it was at this point where all adjustments could be made to eliminate any future errors in the data set. The pilot survey also indicated whether or not the relevant data could be extracted from the camera angles available. The second critical phase of the survey process was that a full week survey was done, this was done to establish the critical peak day which would eventually be used to calculate the critical peak hour for the centres analysed as well as the peak hour factors. The aim of establishing a peak day for the various centres was to eliminate unnecessary data collection and cost, also to focus the study on peak data which will later be compared against prescribed peak rates for these types of developments. Once the peak day was established, phase three was to undertake the final surveys for each individual site and phase four was implemented in order to strengthen the outcomes of the data set, the approach of a repetitive assessment approach (three separate surveys at each site) was used. Based on the weekly peak analysis done, it is evident that the Saturday peak is to be considered the critical/maximum peak for the week. A further conclusion of the weekly peak analysis is that the weekend (Saturday and Sunday) traffic pattern differs from the weekday pattern as it is structured around a single critical morning to midday peak, with the no secondary peaks encountered as with the weekday traffic patterns. The analysis done indicates that TND development principals have a greater impact on the modal split (or preferred mode choice) than TOD as the number of pedestrian trips far exceeds the number of public transport trips generated. This trend was conclusive for all 3 sites used as part of the investigation. A firm conclusion can be drawn from modal split analysis when assessing these developments. When the development form is adequately structured around a pedestrian movement and accessibility (TND type developments), one of the main benefits are increased pedestrian traffic. The outcomes of the modal split analysis also show a positive trend when using the TOD design approach, with the benefits of increased public transport trips. When assessing all the results achieved in the trip generation comparative analysis, it can be concluded that the COTO rate is an accurate prediction for low income shopping centre developments which are built along a transport corridor (TOD design element) and which are pedestrian friendly developments (TND design element). The NDoT calculated rates are not considered appropriate for these developments as they are way in excess of the actual rates recorded.